2011
DOI: 10.5194/hess-15-1339-2011
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective automatic calibration of hydrodynamic models utilizing inundation maps and gauge data

Abstract: Abstract. Automatic and multi-objective calibration of hydrodynamic models is -compared to other disciplines like e.g. hydrology -still underdeveloped. This has mainly two reasons: the lack of appropriate data and the large computational demand in terms of CPU-time. Both aspects are aggravated in large-scale applications. However, there are recent developments that improve the situation on both the data and computing side. Remote sensing, especially radarbased techniques proved to provide highly valuable infor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 46 publications
1
104
0
3
Order By: Relevance
“…The multi-objective calibration by Dung et al (2011) showed that the model could satisfyingly simulate the inundation extent only, if the model dyke levels were lowered by 20 %. This indicated that the dyke level data were not accurate.…”
Section: Hydrodynamic Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…The multi-objective calibration by Dung et al (2011) showed that the model could satisfyingly simulate the inundation extent only, if the model dyke levels were lowered by 20 %. This indicated that the dyke level data were not accurate.…”
Section: Hydrodynamic Modellingmentioning
confidence: 99%
“…2). A comprehensive description of how floodplain compartments are introduced by the "virtual" channels and wide cross sections can be found in Dung et al (2011). The model has been calibrated by Dung et al (2011) …”
Section: Hydrodynamic Modellingmentioning
confidence: 99%
See 3 more Smart Citations